Attractive or Credible Celebrities: Who Endorses Green Products Better? - ERDOĞMUŞ, ZEYNEP İREM (ELSEVIER SCIENCE BV, 2016)
The aim of this study is to measure the impact of celebrity endorsement type (celebrity credibility and attractiveness) and product type (for durable and non-durable product) on attitude towards green advertisement. For this purpose, a 2x2 between subjects factorial design experimental study was utilized. Two different product categories refrigerator (durable) and milk (non-durable) and two different types of celebrities Hulya Avsar (Attractive) and Sener Sen (Attractive) were selected. In order to test the study a Two-Way Factorial ANOVA analysis was used. The results indicated there was a main effect of both product and celebrity type on the attitude towards advertising. In addition, the results indicated that credibility and attractiveness of a celebrity did matter for different types of products. Attitude toward green advertisement increased when the celebrity was credible for milk (nondurable product), and higher for attractive celebrity in refrigerator (durable product). (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Celebrity endoresement; celebrity credibility; celebrity attractiveness; green advertisement; PHYSICAL ATTRACTIVENESS; TRUSTWORTHINESS; COMMUNICATION; CREDIBILITY; HYPOTHESIS; EXPERTISE; PURCHASE